Visceral and somatic pain modalities reveal NaV1.7‐independent visceral nociceptive pathways. (1st March 2017) - Hockley, James R. F.; González‐Cano, Rafael; McMurray, Sheridan; Tejada‐Giraldez, Miguel A.; McGuire, Cian; Torres, Antonio; Wilbrey, Anna L.; Cibert‐Goton, Vincent; Nieto, Francisco R.; Pitcher, Thomas; Knowles, Charles H.; Baeyens, José Manuel; et al.
Abstract : Key points: Voltage‐gated sodium channels play a fundamental role in determining neuronal excitability. Specifically, voltage‐gated sodium channel subtype NaV 1.7 is required for sensing acute and inflammatory somatic pain in mice and humans but its significance in pain originating from the viscera is unknown. Using comparative behavioural models evoking somatic and visceral pain pathways, we identify the requirement for NaV 1.7 in regulating somatic (noxious heat pain threshold) but not in visceral pain signalling. These results enable us to better understand the mechanisms underlying the transduction of noxious stimuli from the viscera, suggest that the investigation of pain pathways should be undertaken in a modality‐specific manner and help to direct drug discovery efforts towards novel visceral analgesics. Abstract: Voltage‐gated sodium channel NaV 1.7 is required for acute and inflammatory pain in mice and humans but its significance for visceral pain is unknown. Here we examine the role of NaV 1.7 in visceral pain processing and the development of referred hyperalgesia using a conditional nociceptor‐specific NaV 1.7 knockout mouse (NaV 1.7 Nav1.8 ) and selective small‐molecule NaV 1.7 antagonist PF‐5198007. NaV 1.7 Nav1.8 mice showed normal nociceptive behaviours in response to intracolonic application of either capsaicin or mustard oil, stimuli known to evoke sustained nociceptor activity and sensitization following tissue damage, respectively. Normal responses following induction of cystitis by cyclophosphamide were also observed in both NaV 1.7 Nav1.8 and littermate controls. Loss, or blockade, of NaV 1.7 did not affect afferent responses to noxious mechanical and chemical stimuli in nerve–gut preparations in mouse, or following antagonism of NaV 1.7 in resected human appendix stimulated by noxious distending pressures. However, expression analysis of voltage‐gated sodium channel α subunits revealed NaV 1.7 mRNA transcripts in nearly all retrogradely labelled colonic neurons, suggesting redundancy in function. By contrast, using comparative somatic behavioural models we identify that genetic deletion of NaV 1.7 (in NaV 1.8‐expressing neurons) regulates noxious heat pain threshold and that this can be recapitulated by the selective NaV 1.7 antagonist PF‐5198007. Our data demonstrate that NaV 1.7 (in NaV 1.8‐expressing neurons) contributes to defined pain pathways in a modality‐dependent manner, modulating somatic noxious heat pain, but is not required for visceral pain processing, and advocate that pharmacological block of NaV 1.7 alone in the viscera may be insufficient in targeting chronic visceral pain. Key points: Voltage‐gated sodium channels play a fundamental role in determining neuronal excitability. Specifically, voltage‐gated sodium channel subtype NaV 1.7 is required for sensing acute and inflammatory somatic pain in mice and humans but its significance in pain originating from the viscera is unknown. Using comparative behavioural models evoking somatic and visceral pain pathways, we identify the requirement for NaV 1.7 in regulating somatic (noxious heat pain threshold) but not in visceral pain signalling. These results enable us to better understand the mechanisms underlying the transduction of noxious stimuli from the viscera, suggest that the investigation of pain pathways should be undertaken in a modality‐specific manner and help to direct drug discovery efforts towards novel visceral analgesics.